2014
DOI: 10.1536/ihj.13-370
|View full text |Cite
|
Sign up to set email alerts
|

The Difference of Predictors for Recurrence After Catheter Ablation of Non-Paroxysmal Atrial Fibrillation According to Follow-Up Period

Abstract: SummaryThe aim of this study was to assess the clinical and echocardiographic predictors for the recurrence of persistent atrial fibrillation (AF) after ablation during a long-term period.A total of 130 patients with persistent AF who had undergone radiofrequency catheter ablation (RFCA) were enrolled. We analyzed the relation between clinical parameters, echocardiographic parameters, and AF recurrences at 6 months, 1 year, and 2 years after ablation.During the 2-year follow-up, AF recurred in 61 patients (46.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…20,21) Although many patients with late recurrence after PAF ablation had reconnected PVs, a smaller percentage of patients undergoing repeat procedures for AF recurrence were found to have non-PV foci that may not have been identified or targeted during the initial procedure. 22) About 4% to 42% of patients having repeat ablation procedures for paroxysmal AF need ablation of non-PV foci during the follow-up procedure.…”
Section: Discussionmentioning
confidence: 99%
“…20,21) Although many patients with late recurrence after PAF ablation had reconnected PVs, a smaller percentage of patients undergoing repeat procedures for AF recurrence were found to have non-PV foci that may not have been identified or targeted during the initial procedure. 22) About 4% to 42% of patients having repeat ablation procedures for paroxysmal AF need ablation of non-PV foci during the follow-up procedure.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 More importantly, the role of reduced LAAEFV in thrombogenesis and stroke has been studied fairly well [7][8][9][10][11] and available data suggest that it may also be correlated with endpoints regarding rhythm control. Indeed, higher LAAEFV has been suggested to be an independent predictor of sinus rhythm maintenance after electrical cardioversion, 12 radiofrequency (RF) ablation for paroxysmal or persistent AF, 4,[13][14][15][16][17] or balloon cryoablation for paroxysmal AF. 18,19 In the present study, we sought to prospectively evaluate LAAEFV changes in a short-term follow-up period (…”
Section: Introductionmentioning
confidence: 99%
“…2,3) Doppler transesophageal echocardiography (TEE) measurement of blood flow velocity in the left atrial (LA) appendage (LAA) and the presence of LA spontaneous echocardiographic contrast (LASEC) have been used to assess the severity of blood stasis, a risk factor for thrombus formation and stroke. [4][5][6] Previous reports have shown that dense LASEC, decreased LAA flow velocity (LAA-FV), and complex aortic plaques on TEE are independent risk factors for subsequent thromboembolic events. [7][8][9] Although TEE yields high-resolution dynamic images of LA, 4,10) this method is relatively invasive and low-throughput.…”
mentioning
confidence: 99%